(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
We sought to address, objectively and from a medical and legal perspective, the types of civil incapacity that give rise to a person’s judicial interdiction, as well as the main aspects involving the and some points relating to the judicial interdiction action, taking into account the current legal system, the new Code of Civil Procedure and the changes to the Civil Code made by the recent Statute for People with Disabilities.